2010
DOI: 10.3855/jidc.541
|View full text |Cite
|
Sign up to set email alerts
|

Using poly-N-acetyl glucosamine gel matrix to deliver IL-12 with anti-schistosomasis vaccination

Abstract: Background: Interleukin (IL)-12 is a potential adjuvant in a variety of diseases including schistosomiasis. The clinical use of IL-12, however, is limited by the toxicity associated with its systemic administration. We have developed a novel delivery system (designated F2 gel matrix) composed of poly-N-acetyl glucosamine that has the dual properties of sustaining the release of proteins (e.g. interleukins) and adjuvant effects. The main aim of this study was to use a mouse model to test whether IL-12 released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Regarding SLAP plus IL12 vaccine, it gave better results than artesunate 3 weeks post infection in the present study with reductions reaching 67.6% in worm burden ,88.7% in mean number of eggs in liver, and 88.8% in mean number of eggs in intestine. This is in agreement with Salem et al [50] who stated that IL12 is a potential adjuvant in many diseases including schistosomiasis.IL-12 increase the cell mediated immunity and Th1 cell response [17]. In another study, Feng et al [51] reported that the worm and egg reduction rates were 64.3% and 79.9% in mice vaccinated by S. japonicum DNA with IL12.…”
Section: Resultssupporting
confidence: 93%
“…Regarding SLAP plus IL12 vaccine, it gave better results than artesunate 3 weeks post infection in the present study with reductions reaching 67.6% in worm burden ,88.7% in mean number of eggs in liver, and 88.8% in mean number of eggs in intestine. This is in agreement with Salem et al [50] who stated that IL12 is a potential adjuvant in many diseases including schistosomiasis.IL-12 increase the cell mediated immunity and Th1 cell response [17]. In another study, Feng et al [51] reported that the worm and egg reduction rates were 64.3% and 79.9% in mice vaccinated by S. japonicum DNA with IL12.…”
Section: Resultssupporting
confidence: 93%
“…A polysaccharide gel matrix, designated F2 gel, is comprised of 70% deacetylated poly-N-acetyl glucosamine (p-GlcNAc) coformulated with lactate salt. p-GlcNAc gels were evaluated as slow-release cytokine depots for GM-CSF, IL-2, and IL-12 (356)(357)(358)(359)(360). In particular, i.t.…”
Section: Chitosan and Poly-n-acetyl Glucosaminementioning
confidence: 99%
“…Natural polymers include proteins like albumin, and polysaccharides like chitosan and poly-N-acetyl glucosamine. [400][401][402] Natural polypeptides possess high biocompatibility but require robust identification, standardization, and purification methods to reduce potential batch-to-batch variation. Polymers derived from natural sources can also be immunogenic, which hinders their performance.…”
Section: Biodegradable Cation Polymersmentioning
confidence: 99%